Senyapan dalam Tuturan Berbahasa Indonesia: Studi terhadap Tuturan pada“Debat Pilkada DKI 2017” - Wira Kurniawati (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2018)
The purpose of this study is to describe the pause in the production of Indonesian speech in terms of duration, percentage, and reason of pause. This data is released on the pause in the speech delivered by the candidate for governor and vice governor in the event of “2017 Governor Candidate Debate of DKI Jakarta